Analisis Kinerja Birokrasi di Pemerintah Daerah Kabupaten Musi Banyuasin (Studi Kasus: Relokasi Pasar Rakyat oleh Dinas Koperasi, UMKM, dan Pengelolaan Pasar Tahun 2016) - Tri Anggraini (Center fo State Civil Apparatus Training and Development and Competency Mapping, 2020)
There was a bureaucratic problem in implementing public traditional market relocation program in Sekayu, Musi Banyuasin Regency. This problem could be explained through Bureaucratic Specialization concept perspective. Hence, this research examined bureaucratic practice, including the cause and challenge of Bureaucratic Specialization using this market relocation case as the background based on bureaucratic performance analysis. Qualitative approach with descriptive method was used in this research. Data was collected through observation and depth interview method. The result was although Bureaucratic Specialization had not achieved its optimum point, it had already caused bureaucracy performance breakdown. It was indicated by negative symptoms such as slow inefficient convoluted bureaucracy and unclear task division. The research suggested that Musi Banyuasin Regency Government should make a clear distinction among its office’s tasks and responsibilities and support its implementation.